1990
DOI: 10.1093/oxfordjournals.humrep.a137153
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromosome analysis in a man heterozygous for a reciprocal translocation 46, XY t(12;20) (q24.3;q11)

Abstract: Sperm chromosome complements were studied in a man who carried a reciprocal translocation t(12;20)(q24.3;q11). A total of 113 spermatozoa were karyotyped after in-vitro penetration of hamster eggs. 2:2 and 3:1 meiotic segregations were observed with the following frequencies: alternate 47%, adjacent 1 42%, adjacent 2 10%, 3:1 2%. For alternate segregations, the number of normal spermatozoa (25) was not significantly different from the number of spermatozoa carrying a balanced form of the translocation (28), as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Analysis of sperm nuclei was employed besides post‐fertilization analysis in blastomers. Most studies on reciprocal translocations showed that normal/alternate and adjacent I segregations are common segregation patterns and their frequencies are similar [Brandriff et al, 1986; Martin et al, 1990b; Templado et al, 1990; Estop et al, 1998; Escudero et al, 2003; Lim et al, 2003]. Our results for the all cases with t(7;10), t(15;17), t(6;13), and t(1;13) were also consistent with the data reported and frequencies of normal/alternate and adjacent I segregations were common (78.6%, 76.8%, 70.5%, and 71.8%) which show that the most important phenomenon in meiosis for chromosome segregation is centromeres.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of sperm nuclei was employed besides post‐fertilization analysis in blastomers. Most studies on reciprocal translocations showed that normal/alternate and adjacent I segregations are common segregation patterns and their frequencies are similar [Brandriff et al, 1986; Martin et al, 1990b; Templado et al, 1990; Estop et al, 1998; Escudero et al, 2003; Lim et al, 2003]. Our results for the all cases with t(7;10), t(15;17), t(6;13), and t(1;13) were also consistent with the data reported and frequencies of normal/alternate and adjacent I segregations were common (78.6%, 76.8%, 70.5%, and 71.8%) which show that the most important phenomenon in meiosis for chromosome segregation is centromeres.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies used BWW medium [Martin, 19831 for capacitation of sperm [Balkan et al, 1983;Balkan and Martin, 1983a, b;Benet and Martin, 1988;Brandriff et al, 1985a;Martin, 1984Martin, ,1986Martin, ,1988aMartin et al, 1986aMartin et al, , 1987Rudak et al, 19781. Test-yolk buffer [Brandriff et al, 1985bl was also used for storage and capacitation of sperm [Brandriff et al, 1985a[Brandriff et al, , 1986Martin, 1988bMartin, , 1990Martin et al, 1990a, b;Templado et al, 19881. Some studies did not clearly identify which type of sperm pretreatment was used [Jenderny and Rohrborn, 1987;Pellestor et al, 1987Pellestor et al, , 1989Sele et al, 19851.…”
Section: Methodsmentioning
confidence: 99%
“…The men were 18 to 55 years old. The mean frequency of numerical abnormalities in the Martin et al, 1990aMartin et al, 1990bMartin, 1984Martin, 1988Balkan and Martin, (unpubl. data) (unpubl.…”
Section: Human Spermmentioning
confidence: 99%
“…However, the incidence of segregation patterns of the balanced reciprocal translocation in sperm nuclei with the hamster oocyte-sperm fertilization technique is highly variable from one translocation to another and also from carrier to carrier (Pellestor Ç ora et al · Sperm-FISH Analysis in Carriers of Translocation 15;17 Blanco et al, 1998). Additionally, some investigators have shown evidence for an increase in the frequency of certain segregation products for some translocations (Pellestor et al, 1989;Martin et al, 1990;Estop et al, 1992). Furthermore, the 4:0 segregation in these studies was reported to be a more rare event.…”
Section: Discussionmentioning
confidence: 99%